Mengapa Inovasi itu Penting? Riset Pada Daya Saing UKM Selama Pandemi Covid-19 - Widyadhana Subiyanto; dekeng setyo budiarto (Universitas Sarjanawiyata Tamansiswa, 2022)
Various research findings have shown that SMEs significantly contribute to economic growth, especially in developing countries. However, the competitiveness of SMEs in facing environmental uncertainty is still a matter of debate. The purpose of this study was to examine the effect of implementing e-commerce, innovation, and payment gateways on the competitiveness of SMEs. This study used a questionnaire addressed to 101 SME owners in the Sleman Regency of Yogyakarta. This study uses non-probability sampling with the criteria that only SMEs use e-commerce to obtain data faster. The survey results prove that innovation has a significant role in increasing the competitiveness of SMEs, besides the use of e-commerce and payment gateways will have an impact on increasing the competitiveness of SMEs facing environmental uncertainty. This research implies a need for government commitment to improve infrastructure, organize training for owners, and provide easy access to financial institutions to strengthen SMEs' performance.